High pressure phase equilibria of the system CO2 + N-dodecane + 3,7-dimethyl-1-octanol + 1-decanol - Latsky, Carla (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.